Maternal and Neonatal Outcome in Postdated Women Undergoing Induction of Labour Versus Spontaneous Labour - I Krishnappa; Y Srinivasa (Asian Journal of Medical Research, 2021)
Background: To compare maternal and neonatal outcome in postdated women undergoing induction of labour versus spontaneous labour. Subjects and Methods: One hundred two females age ranged 18- 46 years of age were selected. Patients were divided into 2 groups of 51 each. Group I were those who had spontaneous labour and group II had induction of labour. Gestational age was assessed by ultrasonography in the first trimester of pregnancy. Results: Mode of delivery was vaginal in 30 in group I and 17 in group II, instrumental in 18 and 4 and LSCS in 3 and 30 in group I and II respectively. Indication for LSCS was non- progression of labour in 36 and 45, cord prolapse in 7 and 1, foetal distress in 8 and 3 and meconium-stained amniotic fluid in 0 and 2 in group I and II respectively. Maternal complications found to be post-partum haemorrhage seen in 4 and 10, perineal tear in 2 and 4 and sepsis in 3 and 5. Neonatal complications were respiratory distress in 3 and 3, meconium aspiration in 1 and 4 and hyperbilirubinemia in 2 and 0 in group I and II respectively. Conclusion: Induction should not be considered as a routine elective procedure. It should be carried out only when necessary.